2016
DOI: 10.1021/acs.inorgchem.6b01259
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Insights into Nanoparticle Formation of Hydroxyfluorinated Anatase Featuring Titanium Vacancies

Abstract: Anatase TiO2 with exposed highly reactive (001) surface is commonly prepared using solution-based synthesis in the presence of a fluorinating agent acting as a structure-directing agent. Recently, the solvothermal reaction of titanium tetraisopropoxide in the presence of aqueous HF has resulted in the stabilization of an oxyhydroxyfluorinated anatase phase featuring cationic vacancies. In the present work, we have studied its formation mechanism, revealing a solid-state transformation of a highly defective ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 24 publications
3
54
0
2
Order By: Relevance
“…At the early stage of the reaction, a large content of titanium vacancies was observed, indicating the predominance of OH – and F – anions over O 2– in Ti 1– x – y ⬜ x + y O 2–4( x + y ) F 4 x (OH) 4 y compounds. This signifies that the titanium alkoxide readily reacted by hydrolysis and fluorolysis reactions, which is similar to what was observed at low temperature ( T = 90 °C) . Thereafter, the vacancy content decreases progressively, indicating a compositional change upon reaction.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…At the early stage of the reaction, a large content of titanium vacancies was observed, indicating the predominance of OH – and F – anions over O 2– in Ti 1– x – y ⬜ x + y O 2–4( x + y ) F 4 x (OH) 4 y compounds. This signifies that the titanium alkoxide readily reacted by hydrolysis and fluorolysis reactions, which is similar to what was observed at low temperature ( T = 90 °C) . Thereafter, the vacancy content decreases progressively, indicating a compositional change upon reaction.…”
Section: Resultssupporting
confidence: 79%
“…Our previous work showed that fluoride is actually incorporated within the anatase's lattice leading to the formation of titanium vacancies, that is Ti 1– x – y ⬜ x + y O 2–4( x + y ) F 4 x (OH) 4 y . For a reaction temperature of 90 °C, a time‐dependent study revealed that first, an hydroxyfluoride composition forms and further evolves through a solid‐state transformation into an oxy‐hydroxyfluoride phase by oxolation reactions . To understand the effect of temperature on the reactivity of titanium alkoxide and HF, a time‐dependent study was performed at higher temperature, that is T = 150 °C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations